A trajetória profissional de Edmar Ferretti: memória e história - Martins, Kelly Aparecida de Paula (2018)
This research brings a study of the professional trajectory of Edmar Ferretti in the form of a professional biography focusing on his artistic activities. The text contains theoretical contributions and methodological reflections about biographical writing and how this writing can be constructed, what materials are needed for its construction, which are discussed in the first chapter. For the development of the professional biography of Edmar Ferretti, the sources used were documents of the personal collection of the biography, such as: programs of his artistic interpretations, newspaper clippings with criticisms about him, photographs and other cataloged files, which served as support for the biographical writing presented in later chapters. The dissertation presents the first musical knowledge of Edmar and its phases of formation in Piano, Song, Actress, as well as its performances in these areas. As a singer, she performed several operas and was considered the best interpreter of the songs of Camargo Guarnieri, besides having interpreted and premiered several works of the composer accompanied by him to the piano. Her activities as a teacher at the Institute of Arts of the Federal University of Goiás and her work at the Federal University of Uberlândia were presented. She was the first teacher to take classes in the Singing Course, beginning in 1981, in addition to her performances as regent with the Coral of UFU, since joining this university.